The Effect of Company Size, Corporate Governance, and Capital Intensity on Tax Aggressiveness - Alicia Sugoro; Grace T. Pontoh; Sri Sundari (Jurnal Ekonomi, 2025)
Companies implement various tax strategies to optimize their tax obligations. This study aims to prove and analyze the effect of company size, independent board of commissioners, institutional ownership, and capital intensity on tax aggressiveness. The data in this study are secondary data obtained from the Indonesia Stock Exchange website. The data collected and met the criteria using purposive sampling technique amounted to 47 energy sector companies for two periods. The data was processed with multiple linear regression analysis. The results of this study indicate that: (1) Institutional ownership has a significant effect on tax aggressiveness; (2) Capital intensity has a significant effect on tax aggressiveness; (3) Company size has no significant effect on tax aggressiveness; (4) Independent board of commissioners has no significant effect on tax aggressiveness; (5) Simultaneously, company size, independent board of commissioners, institutional ownership, and capital intensity have a significant effect on tax aggressiveness.